2023
DOI: 10.1039/d2ta07885f
|View full text |Cite
|
Sign up to set email alerts
|

Super-flexible phase change materials with a dual-supporting effect for solar thermoelectric conversion in the ocean environment

Abstract: Solar thermoelectric generators (STEGs) based on phase change materials (PCMs) are an emerging advanced technology to collect and utilize solar energy. However, it is still challenging for photo-driven PCMs to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…The developed STEGS in ice water also continuously generated output voltage and current for about 810 s without solar irradiation thanks to the latent heat release by the PEG component within the developed composite. According to the above results, the STEGS developed in this study exhibits higher output voltage and current than most of the other STEGSs reported in the literature at the same irradiation intensity as shown in Figure a ,, , and Table S5 (Supporting Information). These results confirm the superior performance of the developed STEGS in solar-thermal-electric conversion and electricity generation.…”
Section: Resultssupporting
confidence: 74%
“…The developed STEGS in ice water also continuously generated output voltage and current for about 810 s without solar irradiation thanks to the latent heat release by the PEG component within the developed composite. According to the above results, the STEGS developed in this study exhibits higher output voltage and current than most of the other STEGSs reported in the literature at the same irradiation intensity as shown in Figure a ,, , and Table S5 (Supporting Information). These results confirm the superior performance of the developed STEGS in solar-thermal-electric conversion and electricity generation.…”
Section: Resultssupporting
confidence: 74%
“…It is inevitable that a small amount of melt leakage still occurs on the surface of these PCMs. 51 Achieving complete leakage-proof performance of flexible PCMs remains a challenge. In this work, the obtained flexible PCMs exhibit excellent leakage resistance due to the dual-supporting effect of the elastic polyurethane (PU) shell of paraffin microcapsules and the three-dimensional NR network.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 Preparing intrinsic flexible phase change materials typically requires the use of a large amount of toxic and harmful reagents (such as toluene), which causes environmental pollution, and the overall enthalpy of the obtained materials is not high. 38 Composite flexible PCMs are usually composed of flexible polymers as the supporting network (such as polyethylene, poly(methyl methacrylate), olefin block copolymers, etc. ), and PCMs are compounded with supporting materials by physical blending.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, flexible shape-stabilized phase change materials, which have the characteristics of flexible processability and nonleakage before and after phase change, have been paid more and more attention recently. Flexible phase change materials (PCMs) can be mainly categorized into two types: intrinsic flexible PCMs and composite flexible PCMs. Intrinsic flexible PCMs are formed by chemically connecting the molecular chains of PCMs with those of flexible polymers, resulting in PCMs with intrinsic flexible phase change properties. , Preparing intrinsic flexible phase change materials typically requires the use of a large amount of toxic and harmful reagents (such as toluene), which causes environmental pollution, and the overall enthalpy of the obtained materials is not high . Composite flexible PCMs are usually composed of flexible polymers as the supporting network (such as polyethylene, poly­(methyl methacrylate), olefin block copolymers, etc.…”
Section: Introductionmentioning
confidence: 99%